Dividend Policy and Its Influence on the Cost of Capital - Shchurina, Svetlana V.; Mustafina, Elvira F. (Journal of Reviews on Global Economics, 2018)
This article conducts a research about the dividend policy of information technology companies with the highest growth rates and a comparison of cash dividends and stock buybacks in terms of cost of capital optimization and increase of enterprise value. In addition, the article presents a comparison between the dividend policy of US and Russian technology companies and concludes that Russian policy is less complicated due to relatively low country market capitalization and short dividend policy background. It is noticed that more and more companies with share equity use share repurchase policy and shorten quantity of cash for dividends payout. Calculation of a number of indexes show that such policy positively influences on the enterprise value, may decrease cost of capital and bring more stability into financial condition of a company.